2013
DOI: 10.4172/2165-7939.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Screw Fixation for Odontoid Fracture Using the Direct Approach at the C2-C3 Level: Case Report and Literature Review

Abstract: Fractures of the odontoid process comprise 10-15% of all cervical fractures. Almost two thirds of all dens fractures are classified as type II according to Anderson and D'Alonso classification system. Currently, the direct anterior odontoid screw fixation provides the best anatomical and functional results for this type of fracture and it is considered as the treatment of choice. Regarding the approach to the C2 vertebra, about 80% of authors usually make a skin incision at the lower cervical level (C4-C5 or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They claimed that this approach avoided excessive tissue damage by retraction or dissection and blind entry of the instruments. However, we found the trajectory through the high incision somewhat problematic with our non-angled instrument set [9]. In spite of being less cosmetically accepted, we found that using a longitudinal incision had the advantages of both low and high incisions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…They claimed that this approach avoided excessive tissue damage by retraction or dissection and blind entry of the instruments. However, we found the trajectory through the high incision somewhat problematic with our non-angled instrument set [9]. In spite of being less cosmetically accepted, we found that using a longitudinal incision had the advantages of both low and high incisions.…”
Section: Discussionmentioning
confidence: 68%
“…Dysphagia usually occurs in the early postoperative period and decreases gradually. It may be related to retraction of pharynx and esophagus or dissection of soft tissues [9]. We tried to ameliorate this problem by loosening the retractor after introducing the k-wire.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 1820 cervical fractures, 340 (19%) were fractures of the axis, 74 (4%) were Hangman fractures, and 199 (59%) were odontoid fractures. A variety of treatment strategies have been proposed for odontoid fractures [8][9][10] and Hangman fractures. [11][12][13] Although treatment overall is controversial, the treatment of axis injuries with multiple fracture lines in particular has very little guidance in the literature and reports of these injuries are only descriptive.…”
mentioning
confidence: 99%